USE OF GLOBAL EXPERIENCES IN THE DEVELOPMENT OF SMALL BUSINESS IN UZBEKISTAN - Rashidov Raxmatillo Alojonovich; Otamirzayev Abduqobil Abdurashid O’g’li; Abduvaliyev Boburshox Ulug’bek O’g’li (Journal of new century innovations, 2023)
Abstract: This in the article small business and private entrepreneurship development directions, small business national in the economy place and importance economic indicators through illuminated. Small business and private entrepreneurship market environment fast adapt getting, employment provide income formation and that's it through his inequality softening and medium the owners layer decision in finding advantages open given